Analysis of The Factors of Conflict Between Student Groups in Makassar City and The Impact on National Security - Thania Novita Damayanti Hutagaol; Bambang Wahyudi; Djayeng Tirto; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
The research aims at finding factors contributing to conflicts between groups of university students, especially that of between the students from Luwu and Bone in 2021. The conflict occurred outside of campus and widely impacted the safety of the surrounding community. The theory employed in the research is The Tree Conflict Model, Conflict Escalation Model, prejudice and stereotype model, and the national security concept. The research applies qualitative method and case study as the research design. Data collection techniques implemented are interviews and literature reviews. The result of the research indicates that conflicts between two student groups are caused by three factors; the Structural, the Manifestation, and the Dynamic factors. The Structural factor is an emotional bonding that gives people sensations of solidarity and causes them to be easily provoked. It also contributes to organizational mishandling and ineffective punishment. In the Manifestation factor, it is the group solidarity that significantly contributes to the conflict. Lastly, it is the Dynamic factor that is reflected in the action of retaliation. More importantly, the impact of the conflict can excess and causes disruption against communal and social safety. In this regard not only is the government responsible for avoiding external threats but it is also mandated for the safety of people in their daily life.